(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article is devoted to a review of the literature on the histogenesis of the lymph nodes of some mammalian species. It has been shown that the lymph nodes perform a specific function for them and participate in the immune response, but their development in each species of mammals has its own characteristics in terms of time parameters.